The physically handicapped and the government : a study of the physically handicapped recipients of Government of India scholarship in Punjab, Haryana, Delhi, and Chandigarh - Mohsini, S. R. (Seema Publications ; Sole distributors, Light and Life, 1982)
Study covers the period 1955-1975/76.